Reanalysis of the Trotter Tibia Quandary and its Continued Effect on Stature Estimation of Past‐Conflict Service Members. Issue 1 (23rd April 2018) - Lynch, Jeffrey James; Brown, Carrie; Palmiotto, Andrea; Maijanen, Heli; Damann, Franklin
Abstract: Forensic casework from past‐conflicts relies on the corrected historical Trotter data for stature estimation in Fordisc. For roughly 10 years', stature estimation using this data has produced point estimates for the tibia that are on average 1.25 inches less than the other long bones. This issue was identified after applying the equations derived from Fordisc to the USS Oklahoma commingled assemblage. Reevaluation of Fordisc revealed that a correction factor of 20 mm, instead of 10 mm, was mistakenly applied to the Trotter tibia data. Historical forensic anthropology reports written at the Defense POW/MIA Accounting Agency were utilized to identify that the overcorrection is isolated to Fordisc 3 with an error rate of 5% of known antemortem statures falling outside of the prediction intervals that relied on the tibia. Further evaluation of the Oklahoma sample indicates the 10 mm correction is still producing point estimates less than the other long bones.